2016
DOI: 10.1002/ps.4211
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance and diminished secondary kill performance of bait formulations against German cockroaches (Dictyoptera: Blattellidae)

Abstract: BACKGROUND Bait formulations are considered the most effective method for reducing German cockroach infestations. An important property of some bait formulations is secondary kill, whereby active ingredient is translocated in insect-produced residues throughout the cockroach population, especially affecting relatively sedentary early instar nymphs. RESULTS Blattella germanica was collected from a location where baits containing hydramethylnon, fipronil, or indoxacarb became ineffective, and these AIs were to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 34 publications
2
39
0
1
Order By: Relevance
“…Our findings are consistent with other studies showing significant indoxacarb (Gondhalekar et al 2013, Ko et al 2016a) and fipronil (Holbrook et al 2003, Chai and Lee 2010, Gondhalekar et al 2011) resistance in German cockroaches. Resistance to indoxacarb and fipronil in the I-IN and D-IL strains are likely the result of prior selection pressure.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with other studies showing significant indoxacarb (Gondhalekar et al 2013, Ko et al 2016a) and fipronil (Holbrook et al 2003, Chai and Lee 2010, Gondhalekar et al 2011) resistance in German cockroaches. Resistance to indoxacarb and fipronil in the I-IN and D-IL strains are likely the result of prior selection pressure.…”
Section: Discussionsupporting
confidence: 93%
“…Sensory mechanisms (olfaction and taste) and insecticide resistance are two factors that play prominent roles in the efficacy of cockroach baits. This study, and a related investigation, have shown that the efficacy of baits can be compromised, resulting in sublethal doses of AI being received by foraging cockroaches and coprophagous nymphs, potentially hastening the evolution of insecticide resistance …”
Section: Discussionmentioning
confidence: 85%
“…D, green line). Thus, the secondary kill properties of bait formulations are considerably affected by available alternative foods, the palatability of food and bait and insecticide resistance, which affect the ingestion of bait by foraging insects, their survival and the amount of feces they deliver to aggregation sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Ko et al . ), there is little information available regarding the efficacy of gel bait formulations against German cockroaches in Iran. The present study was designed to evaluate the efficacy of selected commercial insecticide gel bait formulations against German cockroaches.…”
Section: Introductionmentioning
confidence: 97%